Malawi : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2012)
The Malawi Growth and Development Strategy II (MGDS-II) is a poverty reduction strategy for the period 2006-11, which is aimed at fulfilling Malawi's future developmental aspiration-Vision 2020. The strategy identifies broad thematic areas and key priority areas to bring about sustained economic growth. A striking feature of this strategy is that the various governmental organizations, private sector, and general public are equal stakeholders. However, successful implementation of MGDS-II will largely depend on sound macroeconomic management and a stable political environment.